Anti-diabetic activity of quercetin extracted from Phyllanthus emblica L. fruit: In silico and in vivo approaches - Prabhu Srinivasan; S. Vijayakumar; Swaminathan Kothandaraman; Manogar Palani (Elsevier, 2018)
In this study, molecular interactions of the ligands, quercetin, gallic acid, and metformin with various diabetes mellitus-related protein targets, such as glycogen phosphorylase and peroxisome proliferator-activated receptor gamma, were assessed. It was revealed that quercetin possesses good binding affinity to both targets. Quercetin is a major constituent of methanolic extracts of Phyllanthus emblica fruit. The antihyperglycemic effect of quercetin in streptozotocin (STZ)-induced diabetic rats was examined. The isolated quercetin administered at a dose of 75 mg/kg body weight produced a maximum decrease of 14.78% in blood glucose levels in the diabetic rats after 7 days of treatment. Furthermore, quercetin doses of 50 and 75 mg/kg were shown to significantly improve the profiles of triglycerides, high-density lipoprotein, very-low-density lipoprotein, low-density lipoprotein, and total cholesterol at the end of the study in STZ-induced diabetic rats. The administration of quercetin (25, 50, and 75 mg/kg body weight) daily for 28 days in STZ-induced diabetic rats resulted in a significant decrease in blood glucose and urine sugar levels, with a considerable rise in plasma insulin and hemoglobin levels. Therefore, quercetin is a potential drug with antidiabetic and antihyperglycemic action mediated by changes in the levels of glucose, cholesterol, and triglycerides as indicated by in silico and in vivo studies. Keywords: Bioactive molecules, Glycogen phosphorylase, Molecular docking, Phyllanthus emblica, Quercetin, Albino Wister male rats